2019
DOI: 10.1159/000497165
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Ataxia and Intrathecal Baclofen for the Treatment of Spasticity and Painful Spasms

Abstract: Background: Intrathecal baclofen (ITB) treatment is considered a powerful tool in the management of severe spasticity in neurological conditions such as multiple sclerosis, cerebral palsy, and traumatic spinal cord and brain injury. Objectives: The objective of this study was to assess the effectiveness of the ITB in patients with inherited ataxia suffering from severe painful spasms and/or spasticity. Method: A total of 5 patients with spinocerebellar ataxia 3 or 7 or Friedreich’s ataxia were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Since most trials have important limitations, as previously mentioned, these results on efficacy should be interpreted with caution Spasticity Botulinum toxin administration can be effective [195]. Alternative and/or complementary pharmacological therapies available are phenol blocks [196], baclofen [197], benzodiazepines [198], or gabapentin [199]…”
Section: Ataxiamentioning
confidence: 99%
“…Since most trials have important limitations, as previously mentioned, these results on efficacy should be interpreted with caution Spasticity Botulinum toxin administration can be effective [195]. Alternative and/or complementary pharmacological therapies available are phenol blocks [196], baclofen [197], benzodiazepines [198], or gabapentin [199]…”
Section: Ataxiamentioning
confidence: 99%
“…Intrathecal baclofen (ITB) infusion is accepted as a treatment for spasticity (increased rigidity of muscle secondary to injury), where it has been shown to improve positioning and decrease muscle tone in targeted patients [ 158 ]. One study has shown ITB treatment has beneficial effects in patients with SCA3, SCA7, and Friedreich ataxia who have spasticity and muscle spasms [ 159 ]. From a molecular standpoint, baclofen functions as a GABA B receptor agonist in the central nervous system [ 160 ].…”
Section: Emerging Therapies For Cerebellar Ataxia Impinge On Ion Chan...mentioning
confidence: 99%